Kemampuan Jaringan, Inovasi dan Kinerja Perusahaan - NUR, KHERAYANI; AMRAENI, AMRAENI (Patria Artha University, 2022)
Network capability is an effort for companies to obtain information and resources, as well as complement and collaborate with partners so as to gain greater knowledge and capabilities. Network capabilities provide opportunities for MSMEs to carry out the learning process, transfer knowledge and technology, and increase organizational capacity for sustainable organizational development. The role of the network is very important in MSMEs, through the network small companies can gain access to certain resources, share risks and production costs, accelerate learning, gain speed to market, achieve flexibility and understand competitive advantage. Network capabilities have a close relationship with innovation, through innovation and collaboration with other companies, organizations or companies can adapt to a competitive business environment. The increasingly competitive business environment is today as a result of globalization, so MSMEs need to find ways to ensure their sustainability more than ever. The purpose of this research is to study the potential of network capabilities, and identify the impact of innovation on company performance. This research is expected to be a reference for those who wish to conduct research on the development and improvement of company performance. The findings in this study are companies need to pay attention to network capabilities and innovation can contribute to increasing competitiveness by creating something new.